SOSIALISASI TINGGALAN ARKEOLOGI MASA PERANG DUNIA II, BUNKER DESA AMOITO SIAMA KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Salniwati, Salniwati (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
The aim of this community service is to give information of bunker as historical sites from World War II to the community around Amoito Siama Village, Ranomeeto District, South Konawe Regency through socialization. This activity managed to raising awareness and knowledge in the community about the importance of preserving and conserving historical sites in the village of Amoito Siama. This Community service used a socialization method through material presentations and interactive discussion with the community of Amoito Siama. The socialization material includes the history and important values of bunker as archaeological remains from World War II, together with Amoito Siama community. The result of this activity showed that the enthusiasm and increase the understanding and awareness of the community at Amoito Siama Village related to the urgency of preserving and maintaining the bunker, which is one of the Archaeological sites. In addition, this activity can also encourage activity community participation in effort to preserve the Archaeological remains at Amoito Siama Village.